Interaksi Antara Jumlah Nitrogen Dan Cara Panen pada Pertumbuhan dan Persentase Minyak Nilam yang Dihasilkan pada Panen Pertama - Stefani Daryanto; Sandra Arifin Aziz (Jurnal Ilmu Pertanian Indonesia, 2007)
Patchouli oil is one of major components in perfumery industries as well as incense. Its smell is heavy and strong due to the presence of its major component called patchoulol or patchouli alcohol. However, the production has not stabilized yet because of several factors including cultivation. Experiment was conducted from November 1999-May 2000. Patchouli cuttings were grown in randomized complete block design with four replications. Nitrogen rates for this experiment were 0, 45, 90, and 135 kg ha-1 and three harvesting methods, which were three pairs of youngest leaves, 20 em from the tip and by leaving 20 em stubble from ground. Plant height and number of branches continued to increase significantly linear at higher N rates. There was significant interaction between N rate and harvesting method on wet and dry harvest mass. Effect of N on composite percentage differed for each harvesting method. The yield from three youngest leaves was higher than harvesting 20 em from the tip and leaving 20 em stubble from the ground for 45, 90, and 135 kg ha-1 respectively. Keywords: patchouli oil, nitrogen level, harvesting method